Children's Rights in Norway An Implementation Paradox? - Karl Harald Søvig (Scandinavian University Press (Universitetsforlaget), 2019)
Norway tops international indexes on children's rights but continues to attract criticism for its level of compliance with the Convention of the Rights of Child. This book is the first scholarly attempt to address this implementation paradox. The authors ask: What is the current level of implementation? How can we explain any gap in perceived performance? Can we improve our measurement of children's rights? With the use of quantitative and qualitative methods, the volume examines a wide range of areas relevant to children's rights. These include child protection and sexual violence, detention and policing, poverty and custody proceedings, asylum and disability, sexual orientation and gender identity, and childcare and human rights education. In addition, the book offers a proposal for an alternative statistical approach to measuring Norway's performance. The book's editors conclude by pointing towards the complex set of factors that complicate full realisation and the need for the Government to engage in proper measurement of implementation.